The Representation of Environmental Issues in an EFL Module for Primary School: A Multimodal Analysis - Ibrahim, Muhammad Agung; Damayanti, Ika Lestari (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
By using a qualitative textual analysis with a multimodal approach, this study explores how environmental issues are depicted in the relations of verbal and visual texts of an EFL module for primary school. The data were obtained from an EFL module for the fifth grade made by the EYL Course Design course students at one university in Bandung. In analysing the data, this study utilized three frameworks: Halliday and Mathiessen’s (2014) Transitivity system, Kress and van Leeuwen’s (2006) Visual Grammar, and Royce’s (1998) Intersemiotic Complementarity. The findings show that, by using a story, the module represents three points of drought-related environmental issues: the causes, the effects, and the solutions. The causes are mostly depicted visually by Transactional Action processes in which the Actors use water as the Goal or the Means in excess. The effects are mostly depicted verbally by Mental, Existential, and Relational processes that indicate human need for water. Meanwhile, the solutions are mostly depicted verbally by Material processes in which water (Goal) becomes an element to be saved by the Actors. In terms of complementarity, most of the elements of verbal and visual texts are completed by each other. Hence, encouraging students’ comprehension of the module, especially related to environmental issues, could be expanded by identifying both texts as a single whole.